Policy Strengthening of Professional Zakat: Analysis of Civil Servant Perception Index at the Ministry of Religion of Sidenreng Rappang Regency - Andriyani, Reni Andriyani (JURNAL ILMIAH GEMA PERENCANA, 2023)
This article describe about professional zakat is one of zakat mal and is a very potential of zakat in building of economy. The implementation of professional zakat payment by civil servant of ministry of Islamic Religion of Sidenreng Rappang is still not optimal, as known it about 25.66%. The purpose of this study was to determine the perception index of professional zakat payments for civil servants at the Ministry of Religion of Sidrap Regency and to formulate strengthening policies for professional zakat management. This research method uses a descriptive quantitative approach. The data was obtained using a questionnaire and the data was processed with the help of the SPPS for Windows application version 22.0, namely by processing descriptive analysis data. The research instrument was made based on a Likert scale which was made based on indicators of perception variables namely Attitudes, Motives, Interests, Past Experiences and Expectations which were developed by themselves. The number of respondents was 137 people. The questionnaire was distributed through the help of Google form. The results showed that the index of perceptions of zakat payments for the civil servant profession of the Ministry of Religion of Sidrap Regency was known to be 69.197% or included in the high category. These findings form the basis for strengthening the professional zakat payment policy for civil servants at the Ministry of Religion of Sidenreng Rappang Regency.